QUALITY IMPROVEMENT INJECTION PART OF SET TOP BOX (STB) USING SIX SIGMA METHOD IN ELECTRONIC COMPANY - Dendhy Indra Wijaya; Ade Astuti Widi Rahayu (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2024)
The company pays full attention to product quality. Electronic companies that produce set-top box (STB) products, carry out their business activities implementing a production quality control system, but in reality there is still poor product quality, for this reason the research aims to reduce existing injection part production defects using the six sigma method. There are 5 (five) types of problems as CTQ (critical to quality) that must be improved so that the problem of injection part defects in set-top boxes (STB) can decrease by 50% or 350 ppm (4.89σ) company target. The sigma level of defective injection part products from January to December 2022 is 4.69σ. Analysis and Improvement of all factors causing the occurrence of defective injection part products. The results can make the number of Injection part defects from January to June 2023 reduced to 1,078 units from the total STB production of 3,645,241 units. After the calculation, it is known that the sigma level of defect injection products after improvement is 4.93σ. The improvement sigma level has passed the sigma level target of 4.89σ set by the company. This proves that the improvement has been successful and has an impact on part defect injection Keywords: six sigma; DMAIC; quality improvement; defects; injection part Abstrak Perusahaan memberikan perhatian penuh terhadap kualitas produk. Perusahaan elektronik yang memproduksi produk set-top box (STB), menjalankan kegiatan usahanya menerapkan sistem pengendalian kualitas produksi, namun kenyataannya masih ditemukan kualitas produk yang kurang baik, untuk itu penelitian bertujuan mengurangi cacat produksi injection part yang ada menggunakan metode six sigma. Ditemukan ada 5 (lima) jenis masalah sebagai CTQ (critical to quality) yang harus perbaikan agar masalah defect injection part pada set-top box (STB) dapat turun 50% atau 350 ppm (4,89σ) target perusahaan. Tingkat sigma produk defect injection part dari bulan Januari hingga Desember 2022 adalah 4,69σ. Analisis dan Perbaikan terhadap seluruh faktor penyebab terjadinya produk defect injection part. Hasilnya dapat membuat jumlah defect Injection part dari bulan Januari sampai dengan Juni 2023 berkurang menjadi 1.078 unit dari total produksi STB sebesar 3.645.241 unit. Setelah dilakukan perhitungan diketahui bahwa level sigma produk defect injection setelah dilakukan perbaikan adalah 4.93σ. Level sigma improvement tersebut telah melewati target level sigma 4.89σ yang telah ditetapkan oleh perusahaan. Hal ini membuktikan bahwa improvement telah berhasil dan membawa dampak pada part defect injection. Kata Kunci: enam sigma; DMAIC; peningkatan kualitas; cacat; bagian injeksi